1996
DOI: 10.1007/bf02054684
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the failing ileoanal pouch to reservoir-ileostomy rather than to ileostomy alone

Abstract: We conclude that conversion to a continent ileostomy is a rewarding method of safely eliminating dysfunction of the ileoanal pouch that cannot be corrected by operation. Presumption is, however, that the surgeon is familiar with both methods and that the primary disease is suitable for pouch surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…Conversion of the failed ileal pouch-anal anastomosis to a continent ileostomy is a reasonable alternative. Despite gratifying results with this procedure reported by several authors recently [11][12][13][14], most surgeons seem still to be reluctant to recommend the technique. The postoperative morbidity (the high reoperation rate in particular) has acted as a deterrent; however modifications in the original surgical technique and postoperative management have reduced the risks.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Conversion of the failed ileal pouch-anal anastomosis to a continent ileostomy is a reasonable alternative. Despite gratifying results with this procedure reported by several authors recently [11][12][13][14], most surgeons seem still to be reluctant to recommend the technique. The postoperative morbidity (the high reoperation rate in particular) has acted as a deterrent; however modifications in the original surgical technique and postoperative management have reduced the risks.…”
Section: Discussionmentioning
confidence: 92%
“…Conversion of the failing pelvic pouch to a continent ileostomy (CI) is a well-tried technique that should therefore be an attractive alternative to be considered and discussed with these unfortunate patients [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Others have had a better experience. Hulten et al 24 reported five ileoanal pouch excisions successfully converted to a Kock continent ileostomy (only one patient required removal of the reservoir because of valve slippage), and Ecker et al 25 reported four of five successful conversions. In these studies, the period of follow-up was not stated, which may explain the difference, because in the present series the range of interval between Kock reservoirs formation and excision extend from 4 to 155 months.…”
mentioning
confidence: 98%
“…Patienten mit fehlgeschlagener restaurativer Operation bleibt dadurch sowohl das inkontinente Stoma als auch unnötiger weiterer Darmverlust erspart [5]. Offensichtlich infolge des bereits vorhandenen Pouches erweist sich die Umwandlungsoperation als besonders risikoarm.…”
Section: Selektion Geeigneter Kandidatenunclassified